EVALUASI KINERJA BANGUNAN AKIBAT PENGARUH GEMPA RENCANA PADA STRUKTUR GEDUNG 3 LANTAI BERDASAR SNI 03-1726-2003 - Christiawan, Ignatius (Gema Teknologi, 2010)
Ignatius Christiawan, in this paper explain that In effort fulfill requirement the well building infrastructure, safety of building user such as building avalanche damage as result of earthquake is principal priority. Due to user safety to building avalanche as result of earthquake then it was issued the Procedure of Earthquake Endurance Planning SNI 03-1726-2003 that regulates of planning, build or operates a building. Problem emerge at the building which have the old regulation plan, so it was need evaluation based on the new regulation. Evaluation is conducted at the 3 floor laboratory and lecturing building. Research was focused on performance evaluation of structure on existing condition relate at regulation of the Procedure of Concrete Structure Calculation for the SNI 2847-2002, application for earthquake based on SNI-1726-2002. SAP 2000 is used to analyze the pushover to obtain the building ductility value and the reduction factor value (R) from the building. The result of material test was obtained fo’ existing 17 Mpa and fy existing 390 Mpa. The result of structure performance evaluation was obtained the service limit performance and the building unlimited performance fulfilling condition SNI – 1726 – 2002. Keywords: plan earthquake, evaluation, safety.